Interference with lysophosphatidic acid receptor 5 ameliorates oxidized low-density lipoprotein-induced human umbilical vein endothelial cell injury by inactivating NOD-like receptor family, pyrin domain containing 3 inflammasome signaling. Issue 1 (1st January 2021) - Xu, Ling; Xu, Chaoxiang; Lin, Xiaoxin; Lu, Huiyao; Cai, Yinlian
ABSTRACT: Endothelial cell damage induced by oxidized low-density lipoprotein (ox-LDL) plays an important role in the pathogenesis of atherosclerosis (AS). We aimed to explore the effects of lysophosphatidic acid receptor 5 (LPAR5) on ox-LDL-induced damage of human umbilical vein endothelial cells (HUVECs). After HUVECs exposed to ox-LDL, LPAR5 expression was detected by RT-qPCR and western blotting. Then, LPAR5 was silenced and cell viability was determined with a CCK-8 assay. ELISA was employed to analyze the contents of inflammatory factors. The levels of oxidative stress markers were examined by kits. The expression of proteins related to endothelium function, including CD31, α-SMA, iNOS and eNOS, was evaluated with RT-qPCR and western blotting. Additionally, the effects of LPAR5 deletion on the NLRP3 inflammasome signaling in HUVECs under ox-LDL condition were assessed by determining NLRP3, caspase-1 and ASC expression. Afterward, NLRP3 agonist MSU was adopted for exploring the regulation of LPAR5 on NLRP3 inflammasome signaling in ox-LDL HUVECs injury. Results revealed that ox-LDL led to a significant upregulation in LPAR5 expression. NLRP3 knockdown enhanced cell viability, inhibited inflammation and oxidative stress in HUVECs after ox-LDL exposure. Besides, the expression of CD31 and eNOS was increased while that of α-SMA and iNOS was decreased after LPAR5 silencing. Moreover, interference with LPAR5 remarkably downregulated NLRP3, caspase-1 and ASC expression. Furthermore, MSU addition partially abrogated the inhibitory effects of LPAR5 deletion on the inflammation, oxidative stress and endothelium dysfunction of HUVECs. To conclude, we demonstrated that LPAR5 silencing alleviates ox-LDL-induced HUVECs injury by inhibiting NLRP3 inflammasome signaling.